2019
DOI: 10.1111/pace.13690
|View full text |Cite
|
Sign up to set email alerts
|

Durability of cryoballoon left atrial appendage isolation: Acute and invasive remapping electrophysiological findings

Abstract: Background The left atrial appendage (LAA) has been identified as a potential source of atrial fibrillation (AF) and has been described as the “fifth” pulmonary vein (PV). We report our initial experience in LAA isolation (LAAI) using the cryoballoon (CB) and data on durability of CB‐LAAI. Methods Patients treated with a CB‐LAAI were retrospectively identified. Six weeks after electrical LAAI, patients were scheduled for staged percutaneous LAA closure. During the second procedure, a subset of patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…However, no RCT has shown that LAA closure devices are superior to uninterrupted OAC in preventing thromboembolism after LAAEI and and no data on thromboembolic complication at long‐term follow‐up are available. Albeit, Bordignon et al suggest that when LAAEI is attempted, a CB approach rather than point‐by‐point RFA around the LAA should be considered, we believe that RFA indeed may be a safer strategy since to date no coronary vessel damage and no LPN paralysis have been reported using this ablation modality . Needless to say, RFA can currently be performed without fluoroscopy or contrast agents in a timely fashion.…”
Section: Anticoagulation After Laaeimentioning
confidence: 81%
See 4 more Smart Citations
“…However, no RCT has shown that LAA closure devices are superior to uninterrupted OAC in preventing thromboembolism after LAAEI and and no data on thromboembolic complication at long‐term follow‐up are available. Albeit, Bordignon et al suggest that when LAAEI is attempted, a CB approach rather than point‐by‐point RFA around the LAA should be considered, we believe that RFA indeed may be a safer strategy since to date no coronary vessel damage and no LPN paralysis have been reported using this ablation modality . Needless to say, RFA can currently be performed without fluoroscopy or contrast agents in a timely fashion.…”
Section: Anticoagulation After Laaeimentioning
confidence: 81%
“…We consider that it is worth assessing for LAA dormant conduction using adenosine or isoproterenol and reassess reconnection after a 30 min waiting period. In this series by Bordignon et al, another great concept arise: LAA occlusion only after confirmation of LAAEI with mapping catheter . More data are needed and larger trials are necessary to support this concept.…”
Section: Left Atrial Appendage Electrical Isolationmentioning
confidence: 96%
See 3 more Smart Citations